2006
DOI: 10.1104/pp.105.074666
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacterial Quorum-Sensing Components to Regulate Gene Expression in Plants  

Abstract: We describe an efficient inducible system to regulate gene expression in plants based on quorum-sensing components found in Gram-negative bacteria such as Agrobacterium tumefaciens. These bacteria monitor their own population density by utilizing members of the N-acyl homoserine lactone family as inducers and a transcriptional activator as its receptor. In our study, we utilize the components from A. tumefaciens (i.e. 3-oxooctanyl-L-homoserine lactone [OOHL]) synthesized by the TraI protein and its receptor, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…These data suggested that AHL play an important role in plant bacterial communication and a possible role in pathogen defense, and we decided to analyze the eVect of AHLs on A. thaliana with the primary focus on the transcriptional level. It should be noted that in a recent report You and colleagues did not Wnd a signiWcant induction of genes after spraying leaves with 3-oxo-octanoyl-L-homoserine lactone (OOHL) (You et al 2006). On the other hand, their experimental system diVered from the one we and others (Mathesius et al 2003;Schuhegger et al 2006) used especially regarding AHL application (uptake through roots vs. spraying on leaf surface).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These data suggested that AHL play an important role in plant bacterial communication and a possible role in pathogen defense, and we decided to analyze the eVect of AHLs on A. thaliana with the primary focus on the transcriptional level. It should be noted that in a recent report You and colleagues did not Wnd a signiWcant induction of genes after spraying leaves with 3-oxo-octanoyl-L-homoserine lactone (OOHL) (You et al 2006). On the other hand, their experimental system diVered from the one we and others (Mathesius et al 2003;Schuhegger et al 2006) used especially regarding AHL application (uptake through roots vs. spraying on leaf surface).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, their experimental system diVered from the one we and others (Mathesius et al 2003;Schuhegger et al 2006) used especially regarding AHL application (uptake through roots vs. spraying on leaf surface). Furthermore, the cut-oV You et al (2006) applied to their array data was log § 1, while we worked with log § 0.7. Nevertheless, while our treatments of Arabidopsis with C6-HSL induced clear changes in transcript levels, only a small number of the induced genes were related to or associated with defense.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mimic is a useful tool for manipulating LasR under environmental conditions where the natural signal is ineffective. Acyl-homoserine lactone signaling has been explored as a means for heterologous expression in eukaryotic cells (23)(24)(25). The stability and potency of TP-1 make it an ideal substitute for activating such a system.…”
Section: Discussionmentioning
confidence: 99%
“…RNA samples were given to MOgene for microarray analysis (You et al, 2006). Agilent's technology was used for microarray and each treated sample was hybridized with control and a dye swap was performed.…”
Section: Microarray Analysismentioning
confidence: 99%